2016
DOI: 10.5713/ajas.16.0629
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestibility, and rumen and metabolic characteristics of cattle fed low-quality tropical forage and supplemented with nitrogen and different levels of starch

Abstract: ObjectiveEffects of nitrogen supplementation associated with different levels of starch on voluntary intake, digestibility, and rumen and metabolic characteristics of cattle fed low-quality tropical forage (Brachiaria decumbens hay, 7.4% crude protein, CP) were evaluated using ruminal and abomasal cannulated steers.MethodsFive European×Zebu young bulls (186 kg body weight, BW) were distributed according to a 5×5 Latin square. The following treatments were evaluated: control, supplementation with 300 g CP/d (0:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 28 publications
(42 reference statements)
2
13
0
2
Order By: Relevance
“…Heifers fed PRO had a greater DMD compared to CON heifers. [40] reported supplementation as the main factor associated with increases in DMD. Therefore, because in the present study we did not observe a difference in NDFD between the CON and PRO treatments, supplement intake is likely responsible for the increase in DMD in the PRO compared to the CON animals.…”
Section: Discussionmentioning
confidence: 99%
“…Heifers fed PRO had a greater DMD compared to CON heifers. [40] reported supplementation as the main factor associated with increases in DMD. Therefore, because in the present study we did not observe a difference in NDFD between the CON and PRO treatments, supplement intake is likely responsible for the increase in DMD in the PRO compared to the CON animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, de Oliveira Franco et al. () found that N supplements with different starch levels supplied to a Brachiaria decumbens hay diet (7.4% CP) increased total DMI. Conversely, a partial substitution effect was also found when feeding ad libitum Chloris gayana hay supplemented with either cottonseed meal or fishmeal to Bos indicus cross‐bred steers (McLennan et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…The large increase of DMI observed in Exp I for WS can be attributed to a positive effect of all tested protein supplements. Besides supplying a critical nutrient, N supplementation of very low‐quality roughages such as WS promotes rumen fibre degradation improving rate of passage (McCollum & Horn, ; Arelovich et al., ; Köster et al., ; Mathis et al., ; de Oliveira Franco et al., ; McLennan, Bolam, Kidd, Chandra, & Poppi, ). However, when forage CP content is greater than 7%, the benefit of supplementing protein on voluntary intake appears to be less significant (Mathis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the hindgut selects for microbes that can tolerate bile salts (73), which may inhibit many Gram-negative bacteria such as Bacteroidetes and Fibrobacteres and help to enrich Gram-positive bacteria such as Actinobacteria and Firmicutes (73). In Holstein steer, the foregut and hindgut microbiomes share only 30% of the species (17,20). Thus, in many aspects a fecal microbiome of cattle grazing tall fescue does not represent that of the corresponding rumen.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings do not truly represent the events occurring in the rumen for the following reasons. The feces and rumen harbor distinct microbiomes, sharing ~30% of the species (17,20). The study with the ewes involved the analysis of rumen fluid drawn via orogastric tube insertion.…”
Section: Introductionmentioning
confidence: 99%